Social Adjustment, Life Satisfaction and Mental Health Among Heavy Smokers: Policy and Practice for Healthcare Professionals - Sajid Hassan; Mazhar Iqbal Bhatti; Sher Bahader, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
This research explores the relationship between social adjustment, life satisfaction, and mental health among heavy smokers. Correlation and comparative group design were used in this study. The total sample of the study consisted of 120 participants who were divided into two groups, i.e., younger adults and middle adults. The age range of participants was also divided into two groups i.e., 20-35 and 35-50. It was hypothesized that there would be a significant relationship between social adjustment, life satisfaction, and mental health among heavy smokers. Social adjustment (Cooper & Gath, 1977), Life satisfaction scale (Mehmood, 2013), and General health questionnaire-28 (Goldberg 1978) were used to measure the social adjustment, life satisfaction and mental health among heavy smokers. Results showed positive relationship related to age and income. Further, the results showed that there is no mentaly healthy significant difference between younger adult heavy smokers and middle adult heavy smokers. Moreover, our hypotheses supported the current research model. This study provides an overview of heavy smokers’ mental health as well as highlights areas where further investigation may yield benefits to mental health professionals.